Mechanism and application of exosomes in the wound healing process in diabetes mellitus - Li, Danyang; Wu, Na (Diabetes research and clinical practice, 2022)
•The process of wound healing and the factors affecting the delayed healing of diabetic wounds.•Exosomes promote the recovery of important cellular functions in the process of diabetic wound healing, such as endothelial cells, fibroblasts, macrophages, and keratinocytes.•Exosomes promote diabetic wound healing by inhibiting inflammation, promoting angiogenesis and collagen deposition.•The molecular mechanism of exosomal proteins, miRNAs, lncRNA and circRNA in diabetic wound healing.•The mechanism and application of exosomes combined with various hydrogels, dressings in diabetic wound healing. Poor wound healing can seriously affect the health of patients with diabetes and result in a heavy medical burden. Recently, exosomes have been considered the key substances involved in the healing of diabetic wounds. The important cells related to the process of diabetic wound healing include endothelial cells (ECs), fibroblasts, macrophages, and keratinocytes. Accumulating evidence indicates that exosomes participate in intercellular communication by regulating the expression of biologically functional molecules and modulating the aforementioned cells through various pathways, thereby promoting angiogenesis, collagen synthesis as well as inhibiting inflammation. This article reviews the mechanism of exosomes in the aforementioned cells and their role in diabetic wound healing. This review further discusses the combined use of exosomes and hydrogels or dressings to prolong the residence time of exosomes in wounds. A better understanding of the mechanism through which exosomes participate in wound healing in diabetes and its impact on the wound healing process may provide insights into the future treatment of diabetic wounds.